PENDIDIKAN KARAKTER RASA INGIN TAHU MELALUI PEMBELAJARAN KONSTRUKTIF DALAM KISAH MUSA DAN KHIDIR - Lukmanul Hakim; Ismail Marzuki (Tadarus Tarbawy Jurnal Kajian Islam dan Pendidikan, 2019)
A developed nation is a nation that values education and science. Because without these two things, it is difficult for a nation to wake up or survive the various challenges that have plagued the existence of a nation. Culture of studying is a must-have aspect, so that education and science that are expected to strengthen the existence of a nation can be achieved. To achieve a culture of studying, many components must be nurtured. By making the process of studying science a culture of national character, it is hoped that the phenomenon of civilization distortion can be addressed by the proficiency of knowledge and skills in various lines of life. The Indonesian people seem to have begun to realize the context of this problem. This can be seen with the inclusion of curiosity to be one of the target components for the achievement of the nation's character. In the implementation of curiosity character education becomes its own challenge so that this character can be well embedded. Constructive learning originating from the philosophy of constructiveism seeks to connect and refine the points of knowledge stored within an object of education, so as to form a motivational construction originating from oneself to always be uplifted in search of projected knowledge in accordance with desired ideals. The Koran, which contains many educational concepts, turns out in advance to give an example of how the implementation of constructive learning is carried out. Is the story between the Prophet Musa and the Prophet Kheer explaining the concept of constructivism learning. In his story the character of Moses' curiosity was honed by the education provided by the Prophet Khidir through constructiveism learning methods